Implicaciones éticas del capitalismo y la economía de mercado en la familia: relectura y tareas de la teología moral desde el Documento de Medellín (2018)
This article, inspired by chapter III Family and Demography of the Document of Medellín (1968), warns in the introduction that it is the family who suffers most from the consequences of the "vicious circles" and the transformations that are generated in the economic order. Therefore, the approach is to treat from different levels of analysis the impact of capitalism and the market economy in this essential institution as is the family. Medellín is the inspirer, but the position of the Church will be critically reviewed through the social encyclicals recognizing its prophetic value of denunciation but also its silence, which has meant a legitimacy of this capitalist system.